Design of Information Systems Payroll At PT. SETRA SARI Branch Surabaya - Rifchi Andriyanto; Haryanto Tanuwijaya; Achmad Arrosyidi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. SETRA SARI Branch of Surabaya is a company operates in cleaning service, pest control, Man Power Supply services. PT SETRA SARI branch of Surabaya have some problems in the payroll system. The problem is low validation according to data recording employee present. Because generate manually. Another problem is calculation and management of employees payroll. To solve these problems, then this research offer an information system based on web application that can be used to record employee present data, and to calculated also manage employees payroll in integrated system.  This information system can help PT.SETRA SARI Surabaya Branch can solve record employee present data, and to calculated also manage employees salary in integrated system.Keywords: payroll, information systems, information systems payroll